Comparing dopamine release, uptake, and D2 autoreceptor function across the ventromedial to dorsolateral striatum in adolescent and adult male and female rats. (15th September 2020) - Pitts, Elizabeth G.; Stowe, Taylor A.; Christensen, Brooke A.; Ferris, Mark J.
Abstract: Adolescence is characterized by changes in behavior, such as increases in sensation seeking and risk taking, and increased vulnerability to developing a range of psychiatric disorders, including substance abuse disorders (SUD) and mood disorders. The mesolimbic dopamine system plays an essential role in mediating these behaviors and disorders. Therefore, it is imperative to understand how the dopamine system and its regulation are changing during this period of development. Here, we used ex vivo fast scan cyclic voltammetry to compare stimulated dopamine release and its local circuitry regulation between early adolescent and adult male and female Sprague-Dawley rats. We found that, compared to adults, adolescent males have decreased stimulated dopamine release in the NAc core, while adolescent females have increased dopamine release in the NAc shell, NAc core, and DMS. We also found sex- and region-specific differences in other dopamine dynamics, including maximal dopamine uptake ( Vmax ), release across a range of stimulation frequencies, and autoreceptor regulation of dopamine release. Better understanding how the dopamine system develops during adolescence will be imperative for understanding what mediates adolescent vulnerability to developing psychiatric disorders and how disruptions during this period of reorganization could alter behaviors and vulnerability into adulthood. Highlights: Adolescent male rats have decreased dopamine release in the nucleus accumbens core. Female adolescents have greater dopamine release in several striatal regions. Autoreceptor regulation of dopamine release differs between adolescents and adults.